2021
DOI: 10.13057/biodiv/d220309
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis for agronomic traits contributing to yield in 30 genotypes of soybean

Abstract: Abstract. Karyawati AS, Puspitaningrum ESV. 2021. Correlation and path analysis for agronomic traits contributing to yield in 30 genotypes of soybean. Biodiversitas 22: 1146-1151. To obtain more productive soybean genotypes, it is essential to know the contribution of each agronomic trait to the productivity of soybeans. The purpose of this study was to analyze the correlation and path analysis in thirty genotypes of soybeans (Glycine max (L.) Merrill) for eleven traits. The study was conducted in March-June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Gayacharan et al [37] found a positive correlation with seed yield and seeds per pod in black gram. Karyawati and Puspitaningrum [38] got the similar result in lentil. Tiwari and Lavanya [39] found a significant and positive correlation between seed yield per plant and the number of seeds per pod.…”
Section: Seeds Per Podmentioning
confidence: 53%
“…Gayacharan et al [37] found a positive correlation with seed yield and seeds per pod in black gram. Karyawati and Puspitaningrum [38] got the similar result in lentil. Tiwari and Lavanya [39] found a significant and positive correlation between seed yield per plant and the number of seeds per pod.…”
Section: Seeds Per Podmentioning
confidence: 53%
“…The number of filled pods and seeds significantly affects seed yield per plant (Aondover et al 2013). These characters are strongly associated with increased crop yield per hectare (Karyawati and Puspitaningrum 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The 100-seed weight affects the increase in the soybean harvest index (Hakim and Suyamto 2017). Karyawati and Puspitaningrum (2021) stated that seed yield is only directly correlated with the 100-seed weight and indirectly correlated with the number of pods filled and the number of seeds per plant. Berhanu et al (2021) reported that seed yield significantly correlated with the number of branches, nodes, seeds, and filled pods.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with previous studies by Alake et al [43] and Unigwe et al [44] . Among soybean plants, an indirect correlation is found between parameters of the number of branches, plant height, and fresh weight of seeds [45] . Maturity age is a parameter that affects the weight of dry pods [38] .…”
Section: Relationship Between Agronomic and Disease Traitsmentioning
confidence: 96%